Manual for the preparation and management of projects to be financed by the Common Fund for Commodities (Common Fund for Commodities AmsterdamNL, 2004)
Intends to assist institutions and persons involved in conceptualising and formulating commodity projects for which financing is sought from the Fund. Contains an extended list of commodities which can be supported as well as clarifies which measures would not be financed by the Fund.
Keywords: COMMODITIES